Current state of mental health research in Mozambique: a scoping review protocol - Mariano Joaquim Creyghton Pedro; Castro Ananias Nhamahango; Luciano Jose Mariquele (BMJ Open)
Introduction Mental health is a fundamental component of overall well-being, underpinning our ability to make both individual and collective decisions. In Mozambique, estimates suggest that a significant number of Mozambicans suffer from common mental disorders such as depression and anxiety, yet the majority go undiagnosed and untreated. In recognition of this burden, the Mozambican Ministry of Health had approved the country’s first Mental Health Strategy and Action Plan in 2007, alongside the National Health Policy Mental Health Guidelines (2006–2015). However, the implementation of this plan and strategy has been challenged by a severely limited mental health workforce and fragile infrastructure. Despite these challenges, recent years have seen some progress, including multisite studies and international collaborations aiming to understand the burden of disease and improve services. Yet, the mental health literature in Mozambique remains fragmented, with significant gaps regarding specific population groups, barriers to care and the effectiveness of interventions. This fragmentation highlights the need for a comprehensive scoping review to map the current state of mental health research in the country and to guide future studies, policy development and clinical practice.Methods and analysis This scoping review aims to map the existing scientific literature on mental health in Mozambique over the past 15 years, focusing on study types, target populations, methodological approaches and key findings. Employing a two-stage screening process and both quantitative and a thematic synthesis approach, the review will analyse studies meeting predefined eligibility criteria. A rigorous search strategy will be implemented across identified electronic databases and grey literature sources, including published studies from 2009 to the present. Data will be charted using a standardised form, and information regarding study characteristics, scope of the research, population involved, geographic distribution and reported outcomes/findings will be collected. This scoping review will follow a standard protocol adhering to the methodological framework outlined by Arksey and O'Malley (2005).Ethics and dissemination Ethical considerations involve respecting original authors, maintaining integrity and transparency, managing data ethically and disclosing conflicts of interest. Dissemination will occur through publication in peer-reviewed journals, conference presentations, open-access repositories, policy briefs, stakeholder engagement activities and social media platforms.Registration details Open Science Framework DOI 10.17605/OSF.IO/8R2P7.